2018
DOI: 10.1002/adfm.201800135
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Photothermal and Photoacoustic Efficiencies for Semiconducting Polymer Nanoparticles through Simply Molecular Engineering

Abstract: Semiconducting polymer nanoparticles (SP NPs) are employed as efficient nanoagents for "all-in-one" theranostic nanoplatforms with dual photoacoustic imaging (PAI) and photothermal therapy (PTT) functions based on their photothermal conversion effect. However, the mechanisms of tuning the PTT efficiency are still elusive, though several SP NPs with high photothermal efficiency are reported. Herein, two donor-acceptor (D-A) SP NPs PTIGSVS and PIIGSVS with the same donor unit but different acceptor units are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…In the past decades, photodynamic therapy (PDT) and photothermal therapy (PTT) for cancer treatment have attracted much attention due to their advantages of tenderness, security and noninvasiveness. [ 1 ] Various nanoagents have been developed for PDT/PTT under near‐infrared (NIR) laser irradiation, including carbon nanomaterials (e.g., carbon dots [ 2 ] and carbon nanotubes [ 3 ] ), organic/polymeric semiconductors, [ 4–6 ] transition metal compound (e.g., ZnPc [ 7 ] and MoS 2 nanoparticles (NPs) [ 8 ] ), metal nanomaterials (e.g., gold nanoparticles [ 9 ] ), black phosphorus nanomaterials, [ 10 ] and biomolecular self‐assembly materials [ 11–13 ] . since the NIR irradiation can provide high penetration and minimal invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, photodynamic therapy (PDT) and photothermal therapy (PTT) for cancer treatment have attracted much attention due to their advantages of tenderness, security and noninvasiveness. [ 1 ] Various nanoagents have been developed for PDT/PTT under near‐infrared (NIR) laser irradiation, including carbon nanomaterials (e.g., carbon dots [ 2 ] and carbon nanotubes [ 3 ] ), organic/polymeric semiconductors, [ 4–6 ] transition metal compound (e.g., ZnPc [ 7 ] and MoS 2 nanoparticles (NPs) [ 8 ] ), metal nanomaterials (e.g., gold nanoparticles [ 9 ] ), black phosphorus nanomaterials, [ 10 ] and biomolecular self‐assembly materials [ 11–13 ] . since the NIR irradiation can provide high penetration and minimal invasion.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the photothermal stabilities of both aza‐BDTP and aza‐BDTP/PTX micelles were carefully studied by comparing their temperature increasing profiles with that of ICG under five repeated cycles of 5 min laser exposure (with 10 min laser off after each cycle) . We found that both aza‐BDTP and aza‐BDTP/PTX micelles showed comparable temperature increases of ≈38–39 °C after each cycle of 785 nm laser exposure at 1.0 W cm −2 (Figure f).…”
Section: Resultsmentioning
confidence: 95%
“…NIR light‐triggered nano‐photothermal agents have been gained widespread focus due to the fact that nano‐photothermal agents can efficiently accumulate into tumors via the typical EPR effect and integrate multimodal therapeutic modalities and imaging components into single nanoplatform for optimized synergistic therapeutic effects . Inorganic nanosystems including metal nanoparticles, carbon‐based nanomaterials, two‐dimensional (2D) nanomaterials (transition metal nanoparticles, transition metal carbides and nitrides (MXenes)) as well as NIR‐absorbing organic nanoparticles such as semiconducting polymers and nanomicelles‐encapsulated organic dyes, have been broadly investigated as photoabsorbing agents for in vitro and in vivo photothermal ablation of cancer cells.…”
Section: Photo‐based Energy‐converting Nanomedicinementioning
confidence: 99%